Matter effect in $P_{μ τ}$ at long baselines - Srubabati Goswami, Supriya Pan, Animesh Chatterjee (SciPost Physics Proceedings, 2025)
In the simple two-generation case, the probability $P_{μ τ}$ is not affected by interactions of neutrinos in matter. But for three-generation case, at baselines of the order of 9000 km, matter effects become important for this channel. This is a genuine three-flavour effect. We study how the presence of non-standard interactions (NSI) alters the $P_{μ τ}$ at these baselines. We observe large deviations from the standard matter effect. In particular, we find energies and baselines for which the phases governing the NSIs do not play any role. This may facilitate a better determination of NSI parameters if tau neutrinos can be detected.